Snow Sports Trauma and Safety: Conference Proceedings of the International Society for Skiing Safety: 21st Volume - Scher, Irving S.; Greenwald, Richard M.; Petrone, Nicola (Springer Nature, 2017)
skiing; snow sports; trauma; safety; kinematics; epidemiology